RUMAH TANGGA MIGRAN DAN KESEHATAN ANAK YANG DITINGGALKAN ANALISA DATA SAKERTI 2007 - Cecep Sukria Sumantri (Jurnal Kawistara, 2013)
This paper discuss about migrant household and the health outcome of the children’s age 0-14 years old. Using data IFLS at 2007, this paper has a purpose knowing the condition of child health at the migrant household where father’s migrant, mother’s migrant, parental migrant, and non migrant household. Using on the data of IFLS at 2007, founded 13.402 respondents at age 0-14 years old. Those are involves 505 children (3,8%) live at migrant father household; 285 children (2,1%) live at migrant mother household; 105 children (0,8%) live at father-mother migrant household and 12.507 children (93,3%) live at non migrant household. The result of this analysis such as: (1) the health status of children left hebind lower than children who’s living with their parent; (2) non migrant household is more educated, because the year of schoolingof household’s head and the caregiver of the children 0-14 years old arehigher than migrant household; (3) the absenteeism of mother on child health status (based on the result of the nurse observation, BMI and Hb level) at migrant mother household is lower than the child health at the others migrant household; (4) household in the urban area gives a positive impact on the health status based on the result of the nurse observation and BMI, but gives negative impact (decrease) on the child’s Hb level; (5) the increase of per capita expenditure gives a significant impact toward the increase of health child status based on the observation of nurse and BMI, but gives the decrease impact on Hb level and BMI after has been interacted by migrant household status.